Effects of Crystallinity and Particle Size on Photocatalytic Performance of ZrTiO4 Nanostructured Powders - Oanh, Le Thi Mai; Ha, Dang Thu; Hue, Man Minh; Hang, Lam Thi; Thang, Dao Viet; Hung, Nguyen Manh; Phuong, Doan Thuy; Minh, Nguyen Van (VNU Journal of Science: Mathematics - Physics; Vol 31 No 4, 2015)
The crystallinity, surface morphology, optical property and photocatalytic performance of ZrTiO 4 nanostructured powders synthesized by sol-gel method at various calcining temperatures were investigated by XRD, FE-SEM, and absorption measurements, respectively. XRD analysis showed that ZrTiO 4 began crystallizing at about 600 °C. The crystallinity increased with increasing calcining temperature. According to FE-SEM images, amorphous particles of nearly 10 nm in size with relatively sphere morphology were formed after a heat treatment of the ZrTiO 4 gel at 450 °C for 3 hours. The crystalline particle size increased gradually to 20, 50, and 100 nm when the calcining temperature increased to 800, 900, and 1000 °C, respectively. The UV-Vis absorption spectra indicated a slight broadening of optical band gap with increasing calcining temperature. Photodegradation performance of Rhodamine B (RhB) in aqueous solution via ZrTiO 4 nanopowders which occurred under the illumination of a Xenon lamp have showed that the ZrTiO 4 sample treated at 800 °C exhibited the largest efficiency of the photocatalytic performance.  Keywords: Nanopowder, photocatalytic, RhB, crystalline, amorphous.